2001
DOI: 10.1039/b104447h
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A homoleptic phosphine adduct of thallium(I) supported by a tris(phosphino)borate ligand has been isolated and structurally characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 10 publications
(7 reference statements)
2
61
0
1
Order By: Relevance
“…The coupling constant to the s-coordinated Tl + ion is almost the same as that with p coordination to give the pseudotriplet signal with a 1 J Tl,P of 305 Hz. Compared to Tl-P coupling constants as found for phosphine adducts of thallium(I), such as 5214 Hz for [Tl{PhB(CH 2 PPh 2 ) 3 }], [16] this value is very low and relates to the low s character of the weakly bonding interactions to the thallium nuclei. A similar small 1 J Tl,P of 500 Hz was found for [Tl 2 {(m,h 4 :h 4 -P 4 (C 6 H 3 dipp 2 ) 2 }] (dipp = 2,6-diisopropylphenyl), in which the tetraphosphabutadiene core is capped by two thallium ions.…”
Section: } 4 ]mentioning
confidence: 82%
See 1 more Smart Citation
“…The coupling constant to the s-coordinated Tl + ion is almost the same as that with p coordination to give the pseudotriplet signal with a 1 J Tl,P of 305 Hz. Compared to Tl-P coupling constants as found for phosphine adducts of thallium(I), such as 5214 Hz for [Tl{PhB(CH 2 PPh 2 ) 3 }], [16] this value is very low and relates to the low s character of the weakly bonding interactions to the thallium nuclei. A similar small 1 J Tl,P of 500 Hz was found for [Tl 2 {(m,h 4 :h 4 -P 4 (C 6 H 3 dipp 2 ) 2 }] (dipp = 2,6-diisopropylphenyl), in which the tetraphosphabutadiene core is capped by two thallium ions.…”
Section: } 4 ]mentioning
confidence: 82%
“…These bonds are fairly long compared to the TlÀP bond lengths in the thallium(I) phosphine adduct [Tl{PhB(CH 2 PPh 2 ) 3 }] (2.878 , 2.953 , 2.932 ). [16] The Tl···Tl distance (5.870 (1) ) is too long to be considered a direct metal-metal interaction. Furthermore, no interactions are found between Tl + and the fluorine atoms of the WCA.…”
Section: } 4 ]mentioning
confidence: 99%
“…The complex is unstable in air and has limited thermal stability, but is an effective ligand transfer reagent for the synthesis of some d-block metal-PNP complexes. Peters and co-workers have prepared several Tl(I) complexes with phosphinoborates [247][248][249][250][251][252]. The diphosphinoborates include [Tl{Ph 2 B(CH 2 PPh 2 ) 2 }] (chain polymer with thallium coordinated 6 to one Ph ring and one -PPh 2 from each of two [Ph 2 B(CH 2 PPh 2 ) 2 ] − ligands) and [Tl{3-MeC 6 H 4 ) 2 B(CH 2 P t Bu 2 ) 2 }] in which the ligand chelates via the two phosphine groups and forms an interaction best described as 2 with the arene ring of another ligand.…”
Section: Thalliummentioning
confidence: 99%
“…Reaction of three equivalents of the phosphinomethide reagent with the desired dichloroborane compound initially gives borate salt formation before the chlorides undergo substitution with two more methides to afford the final ligand as a lithium salt [16][17][18][19][20]. It was found that subsequent metathesis to the thallium salt (using either TlPF 6 or TlNO 3 ) facilitated work up and isolation, as well as acting as a better reagent for further coordination (Scheme 1B) [23]. Only ligands 6 and 7 were not isolated as the thallium salts, instead the lithium salts were used directly in aerosol-assisted chemical vapour deposition experiments [21].…”
Section: Boron (R'b(ch 2 Pr 2 ) 3 -)mentioning
confidence: 96%